2020
DOI: 10.1542/peds.2020-0836
|View full text |Cite
|
Sign up to set email alerts
|

State Insurance Mandates and the Workforce for Children With Autism

Abstract: BACKGROUND: State mandates have required insurance companies to provide coverage for autismrelated child health care services; however, it has not been determined if insurance mandates have improved the supply of child health care providers. We investigate the effect of state insurance mandates on the supply of child psychiatrists, pediatricians, and board-certified behavioral analysts (BCBAs). METHODS: We used data from the National Conference of State Legislatures and Health Resources and Services Administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Insurance mandates that require state-regulated private insurers to offer ASD treatment have been enacted in 50 states (State Regulated Health Benefit Plans, 2020), and 33 states include ASD treatment in their Essential Health Benefits packages sold through the Health Insurance Marketplace (Marketplace Health Insurance, 2019). Indeed, there is evidence that mandates are associated with an increase in the number of BCBAs in a state (McBain et al, 2020). Some states that included many counties with the highest geographic access were among the earliest to pass mandates: Florida (2008); New Jersey and Connecticut (2009); and Massachusetts, Vermont, and New Hampshire (2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insurance mandates that require state-regulated private insurers to offer ASD treatment have been enacted in 50 states (State Regulated Health Benefit Plans, 2020), and 33 states include ASD treatment in their Essential Health Benefits packages sold through the Health Insurance Marketplace (Marketplace Health Insurance, 2019). Indeed, there is evidence that mandates are associated with an increase in the number of BCBAs in a state (McBain et al, 2020). Some states that included many counties with the highest geographic access were among the earliest to pass mandates: Florida (2008); New Jersey and Connecticut (2009); and Massachusetts, Vermont, and New Hampshire (2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, using data from 1999 and 2014, researchers demonstrated that three states-New Jersey, Massachusetts, and Connecticut-have the highest per capita distribution of all BCBAs (Deochand & Fuqua, 2016). The results of the second study reported an association between state health care insurance mandates for the diagnosis and treatment of ASD and an increase in BCBAs (McBain et al, 2020). Finally, in a recent brief report, researchers documented that the per capita supply of certified ABA providers fell below caseload guidelines provided by the Behavior Analyst Certification Board (BACB; Zhang & Cummings, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine the relationship between generosity of state insurance mandates and growth in the health workforce for ASD. While prior studies have examined the effect of mandates on healthcare utilization, spending, and workforce (Barry et al, 2017; McBain, Cantor, et al, 2020), they have focused on mandates as all-or-nothing pieces of legislation and have not accounted for the wide variation in policy features (Callaghan & Sylvester, 2019b; Choi et al, 2020). Our findings show a consistent pattern of results whereby more generous mandates are associated with increased growth in BCBAs and child psychiatrists, indicating that the content of legislation passed may be as important as whether any legislation has been passed.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence also suggests that out-of-pocket spending has increased following the introduction of mandates, though the share of out-of-pocket spending has declined (Candon et al, 2019). In addition, the introduction of mandates has correlated with a modest increase in the supply of autism-related health care: McBain, Cantor, and colleagues (2020) found that mandates were associated with a 16% increase in board-certified behavioral analysts (BCBAs) who provide ABA, and 7% increase in child psychiatrists. From a classical economic perspective, lowering the financial burden of care to families resulting from mandates should lead to greater care seeking and higher provider wages in the short run which, in turn, stimulates providers to enter the market or move to states with mandates in the long run (Dave & Fernandez, 2015; Mankiw, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as demand for behavior analysts increases (BACB, 2020c) and the rise of insurance funding and mandates compel clinics to prioritize activities related to reimbursement and the maximization of billable hours (McBain et al, 2020;Sundberg, 2016), practitioners may find that they allocate more of their weekly hours on client and clinical concerns and have less time for staying in contact with the contemporary behavior-analytic literature. Therefore, good habits and powerful systems-level solutions are needed to ensure behavior analysts are prioritizing time to monitor and consume relevant literature.…”
Section: Barriersmentioning
confidence: 99%